1999
DOI: 10.1007/bf01279261
|View full text |Cite
|
Sign up to set email alerts
|

RGD-mediated membrane-matrix adhesion triggers agarose-induced embryoid formation in sunflower protoplasts

Abstract: Summary. Agarose embedding of sunflower (Helianthus annuus L.)hypocotyl protoplasts induces an asymmetric division pattern and subsequent polarized development leading to embryoid formation. We cultured protoplasts in media with different mannitol concentrations. Induction of plasmolysis of agarose-embedded protoplasts by increasing the mannitol concentration lowered the proportion of embryoids formed. This indicates that adhesion sites between the plasma membrane and the agarose matrix are involved in embryoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…Integrins are also chosen by pathogens as targets for binding, and the RGD motif is present in surface proteins of several pathogens that attach to mammalian cells [5]. In plants, synthetic peptides containing the RGD motif can disrupt the adhesion between plasma membrane and cell wall [6][7] and can interfere with physiological processes thereby affecting, e.g., development [8][9][10][11], mechano-perception [12] and the interaction with microorganisms [13][14][15]. In particular, expression of cell wall associated defence responses triggered by fungal pathogens is dependent on adhesion between the plasma membrane and the plant cell wall [15].…”
Section: Introductionmentioning
confidence: 99%
“…Integrins are also chosen by pathogens as targets for binding, and the RGD motif is present in surface proteins of several pathogens that attach to mammalian cells [5]. In plants, synthetic peptides containing the RGD motif can disrupt the adhesion between plasma membrane and cell wall [6][7] and can interfere with physiological processes thereby affecting, e.g., development [8][9][10][11], mechano-perception [12] and the interaction with microorganisms [13][14][15]. In particular, expression of cell wall associated defence responses triggered by fungal pathogens is dependent on adhesion between the plasma membrane and the plant cell wall [15].…”
Section: Introductionmentioning
confidence: 99%
“…Although early efforts to find functional homologs of integrins in plants proved difficult, the recent demonstration of highaffinity RGD binding sites in the plasma membrane of Arabidopsis (Canut et al, 1998), the recent cloning of a gene from Arabidopsis with partial sequence similarity to integrins from fungi, insects, and humans (Nagpal and Quatrano, 1999), and the discovery of Arabidopsis genes that are predicted to contain ␤ -integrin-like domains (Laval et al, 1999) all suggest that there may be at least some conservation between proteins involved in plasma membrane-ECM interactions in plant and animal systems. Further evidence of similarity between these systems is provided by the fact that treatment with RGD-containing peptides can influence several physiological events in plants (Schindler et al, 1989;Wayne et al, 1992;Barthou et al, 1999). RGD peptides also have been shown to cause a loss of plasma membrane-cell wall adhesion in plasmolyzed Arabidopsis cells and a loss of the thin plasma membrane-cell wall connections known as Hechtian strands that form during onion cell plasmolysis (Canut et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…This was the reason why this study was undertaken to assess the effects of haemoglobin. Previously it was demonstrated that immobilization of sunflower protoplasts in agarose can also stimulate the development of embryo-like structures (Alibert 1997;Barthou et al 1998). It might be concluded that better oxygenation of sunflower protoplasts in culture does increase total number of embryo-like structures but it is not a key factor for further embryo development.…”
Section: Resultsmentioning
confidence: 98%